Floral nectar secretion dynamics of Pavonia urens (Malvaceae) and honey production potential - TURA BAREKE; ADMASSU ADDI (Smujo International, 2024)
Abstract. Bareke T, Addi A. 2024. Floral nectar secretion dynamics of Pavonia urens (Malvaceae) and honey production potential. Nusantara Bioscience 16: 89-95. The honey production potential of honey plant is estimated using the total floral nectar secretion potential of the plant foraged by honeybees within a given location. The current study aimed to determine the floral nectar secretion dynamics of Pavonia urens Cav. in addition to estimating the potential amount of honey that can be produced thereof. Nectar volume (using micropipette), nectar concentration (using digital refractometer), temperature, and humidity (using thermo hygrometer) were measured at 3 h intervals. Nectar volume and concentration differed significantly at different time points throughout the day. Also, nectar volume and concentration differed annually. There was a positive correlation between nectar volume and humidity as well as between temperature and nectar concentration. The mean nectar volume per 24 hours of P. urens was 7.23±0.43 µL. Individual flowers continuously secreted nectar for about 10 days throughout flower life. During each flowering season, an average of 823.5 mg g-1 of honey was generated per plant. Additionally, the average honey production capacity of P. urens was 35 kg ha-1. This suggests that P. urens has the capacity to produce honey; therefore, for sustainable honey production, plating and in-situ conservation of this plant are recommended.